2021
DOI: 10.1002/ajmg.a.62229
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sleep‐disordered breathing and its relationship with respiratory parameters in children with mucopolysaccharidosis Type IVA and VI

Abstract: The aims of the study were to evaluate the prevalence of sleep-disordered breathing (SDB) by using polysomnography (PSG) in children with MPS IVA and MPS VI who underwent enzyme replacement therapy (ERT) and to analyze the effect on SDB of having upper airway surgery, pulmonary functions, and exercise capacity. A retrospective cross-sectional study was conducted on patients with MPS IVA (n:17) and MPS VI (n:11) aged under 19 years who underwent polysomnography. Descriptive and nonparametric analyses were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Mucopolysaccharidoses (MPS) are a group of inherited lysosomal storage disorders caused by an error in the catabolism of glycosaminoglycans (GAGs), with a consequent build-up of mucopolysaccharides in multiple tissues [ 109 ]. An increased prevalence (range, 68–95%) of OSA, demonstrated by polysomnography and nocturnal oximetry, is reported in infants with MPS, often associated with sustained hypoventilation and/or central apnea [ 12 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ]. Obstructive SDB occurs as a consequence of increased upper airway resistance due to the multilevel skeletal, oral, adenotonsillar, laryngeal, and tracheal involvement, reported in all MPS types, with minor relevance for MPS III [ 109 , 118 ].…”
Section: Children With Complex Disordersmentioning
confidence: 99%
See 3 more Smart Citations
“…Mucopolysaccharidoses (MPS) are a group of inherited lysosomal storage disorders caused by an error in the catabolism of glycosaminoglycans (GAGs), with a consequent build-up of mucopolysaccharides in multiple tissues [ 109 ]. An increased prevalence (range, 68–95%) of OSA, demonstrated by polysomnography and nocturnal oximetry, is reported in infants with MPS, often associated with sustained hypoventilation and/or central apnea [ 12 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ]. Obstructive SDB occurs as a consequence of increased upper airway resistance due to the multilevel skeletal, oral, adenotonsillar, laryngeal, and tracheal involvement, reported in all MPS types, with minor relevance for MPS III [ 109 , 118 ].…”
Section: Children With Complex Disordersmentioning
confidence: 99%
“…Until a few years ago, the literature describing the incidence of OSAS in MPS was mainly based on cross-sectional analyses of small cohorts of patients prior to the initiation of treatment (haemopoietic stem cell transplantation—HSCT, enzyme replacement therapy—ERT) and without standardized criteria to define OSA [ 112 , 113 ]. More recent studies, methodologically more homogeneous (OSA defined for an obstructive AHI > 1.5/h), confirm a prevalence of OSA, ranging from 69.8% to 95.2% [ 115 , 116 , 117 ]. In a recent meta-analysis in 2021, the prevalence and profile of sleep disorders in rare genetic syndromes confirmed that SDB was most prevalent in MPS disorders (72–77%) compared to other syndromes mentioned above, such as DS and PWS.…”
Section: Children With Complex Disordersmentioning
confidence: 99%
See 2 more Smart Citations